Novel one-pot Mannich-type reaction in water: Indium trichloride-catalyzed condensation of aldehydes, amines and silyl enol ethers for the synthesis of β-amino ketones and esters - Loh, T.-P. (2014)
10.1016/S0040-4039(97)10478-6